ESP IN PRACTICE: EFFECTIVE STRATEGIES FOR TEACHING ENGLISH IN SPECIALIZED FIELDS - Iskenderova Kamola Azamatovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
ABSTRACT This article examines the practical application of English for Specific Purposes (ESP) in teaching English tailored to the linguistic and communicative needs of learners across various professional and academic disciplines. Drawing on contemporary research and theoretical frameworks, it discusses key teaching strategies, including needs analysis, task-based learning, content-based instruction, authentic materials, and technology integration. The article also examines challenges faced by ESP practitioners and offers evidence-based recommendations for effective curriculum design and classroom practice. Findings indicate that ESP bridges the gap between general English proficiency and specialized communication competencies in fields such as medicine, engineering, business, and law. The study concludes that ESP instruction requires innovative, learner-centered pedagogies and multidisciplinary collaboration to prepare learners for professional success.